The Sovereign Mind: Integrating Ashokan Dhamma-Ethics and Meditative Knowledge Systems for Holistic Mental Wellbeing (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper examines the relationship between the socio-political ethics of Emperor Ashoka and the meditative traditions of Ancient India through the lens of traditional Indian Knowledge Systems (IKS). While classical traditions such as Yoga and Buddhism developed internal techniques for mental regulation through Dhyana (meditation), Ashoka’s Edicts established an external ethical framework (Dhamma) that enabled these practices to function at a societal scale.Drawing on epigraphic evidence in Magadhi Prakrit alongside Yogic and Buddhist textual traditions, the study proposes that Ashoka’s governance model constituted a form of state-supported psychological infrastructure. Interpreted through modern frameworks such as Post-Traumatic Growth (Tedeschi & Calhoun, 2004) and environmental psychology (Wilson, 1984), this paper argues that the Mauryan state cultivated conditions conducive to both individual and collective mental wellbeing. In doing so, it offers a historical model for integrating ethical governance with mental health policy.The contemporary crisis of mental health is often characterized by what Mark Fisher (2009) termed "capitalist realism," where distress is privatized and treated as a chemical imbalance rather than a systemic failure. In contrast, the Mauryan Empire under Ashoka Maurya (r. 268–232 BCE) offers a historical precedent for a "Therapeutic State." Ashoka’s "Dhamma" was not a conversion to a religion in the modern sense, but a sophisticated public health intervention. As Thapar (1997) argues, Dhamma was a "civic ethic" designed to integrate a diverse population. However, when viewed through the lens of Indian Knowledge Systems (IKS), it becomes clear that Ashoka was implementing a "Top-Down" cognitive behavioral framework.